2021
DOI: 10.1007/s13300-021-01031-z
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic Control with Insulin Glargine 300 U/mL in Individuals with Type 2 Diabetes and Chronic Kidney Disease: A REALI European Pooled Data Analysis

Abstract: Introduction: Management of type 2 diabetes mellitus (T2DM) in patients with chronic kidney disease is complex. Using the REALI European pooled database, we determined the impact of baseline renal function on the effectiveness and safety of insulin glargine 300 U/mL (Gla-300) initiated in adults with inadequately controlled T2DM. Methods: Data from 1712 patients with available estimated glomerular filtration rate (eGFR) at baseline were pooled from six 24-week prospective studies. Patients who received once-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…Hypoglycemia incidence over the 24 weeks was similar across both the treatment arms; thus, suggesting better effectiveness of Gla-300 over IDeg-100 without compromising safety [ 18 ]. A recent report from REALI CKD pooled analysis also demonstrated concordant observations in terms of the clinically significant glycemic control with favorable hypoglycemia risk in a diverse group of renal function subgroups (baseline eGFR: ≥90, 60-89, 45-59, and 15-44 mL/min/1.73 m 2 ) indicating no influence of baseline renal function on the effectiveness and safety of Gla-300 during six months of treatment in individuals with poorly controlled T2DM [ 19 ]. Further additional studies in individuals with more advanced renal impairment (eGFR <45 or <30 mL/min/1.73 m 2 ) would be useful.…”
Section: Gla-300 In Special Populationmentioning
confidence: 78%
“…Hypoglycemia incidence over the 24 weeks was similar across both the treatment arms; thus, suggesting better effectiveness of Gla-300 over IDeg-100 without compromising safety [ 18 ]. A recent report from REALI CKD pooled analysis also demonstrated concordant observations in terms of the clinically significant glycemic control with favorable hypoglycemia risk in a diverse group of renal function subgroups (baseline eGFR: ≥90, 60-89, 45-59, and 15-44 mL/min/1.73 m 2 ) indicating no influence of baseline renal function on the effectiveness and safety of Gla-300 during six months of treatment in individuals with poorly controlled T2DM [ 19 ]. Further additional studies in individuals with more advanced renal impairment (eGFR <45 or <30 mL/min/1.73 m 2 ) would be useful.…”
Section: Gla-300 In Special Populationmentioning
confidence: 78%
“…The sub-analysis of the BRIGHT study (Gla-300 vs IDeg-100) and post-hoc analysis from the EDITION program (Gla-300 vs Gla-100) indicated that Gla-300 provided glycaemic control similar to Gla-100 with a reduced overall risk of hypoglycaemia, while Gla-300 provided better glycaemic control compared with IDeg-100 in insulin-naïve PwT2D and with impaired renal function [ 61 , 63 ]. In addition, the results from the REALI CKD pooled analysis also showed that individuals with inadequately controlled T2D and renal impairment who were initiated on or switched to Gla-300 achieved a clinically important improvement in glycaemic control with a low risk of hypoglycaemia [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…42 In April 2021, a real-world pooled analysis of six multicentre, open-label studies of IGla-300 in people with CKD was published. 43 It analysed 1712 participants with T2D and different degrees of renal function from 13 European countries. IGla-300 insulin was initiated, and efficacy and safety were measured after 24 weeks through HbA 1c and the incidence of hypoglycaemia.…”
Section: Insulin Glargine 300 U/mlmentioning
confidence: 99%
“…In April 2021, a real‐world pooled analysis of six multicentre, open‐label studies of IGla‐300 in people with CKD was published 43 . It analysed 1712 participants with T2D and different degrees of renal function from 13 European countries.…”
Section: Second‐generation Basal Insulin Analogues In Ckdmentioning
confidence: 99%